PEMBUATAN MODUL PEMBELAJARAN RANGKAIAN ELEKTRONIKA DIGITAL - Mila Sri Devi; Thamrin Thamrin (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The purpose of this study was to determine the feasibility of using the learning module of the Electronic Electronics Series on the subject of Basic Electricity and Electronics in class X Electronics Engineering at SMK Negeri 1 Bukittinggi. This research method uses the development of Instructional Development Institute with three stages, namely define, development, and evaluation. The research instruments were in the form of questionnaires on validity, reliability and practicality of the module. Based on the results of 3 validators obtained an average of 0.82 from the rating scale 1, which exceeds the achievement level of 0.667, so the module is declared valid. In the module reliability test the Cronbach Alpha value was 0.804, which means the reliability of the module in the category is very high. In the module practicality test by the teacher obtained an average value of 85.83%, so it is in the practical category. While the module practicality test by students obtained an average value of 87%, so it is in a very practical category. Based on the results of the three tests it can be concluded that the learning module is suitable for use in the learning process.Keywords:Module, Electronics Digital, instructional Development Institute